Исследование стационарного нагрева изолированного проводника с током при открытой прокладке в трубах - Dmitrichenko Александр; Yanovskiy С.; Chaychits Николай (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
A mathematical model of stationary heating of the isolated conductor, when laying exposed in the pipes. The model takes into account the heat transfer by radiation, thermal diffusivity and convection, which permits more accurate simulation of the thermal processes. Experimental studies was carried out which confirm the accuracy of the developed model.